2009
DOI: 10.1097/ana.0b013e3181920d28
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine Prevents Transient Cognitive Dysfunction After Moderate Hypoxia in Adult Mice

Abstract: NIMO reverses the disturbance of short-term working memory caused by moderate hypoxia in mice. The results may have implications for cognitive changes linked to Ca homeostasis in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…It has been shown that a relationship exists between changes in cognitive function and hippocampal damage, and that nimodipine treatment reversed the impairment of shortterm working memory caused by moderate hypoxia in mice. 32 Studies on the effect of nimodipine on rats with vascular dementia are, however, scarce. 18 The present study evaluated the effect of nimodipine treatment on levels of NF-κB, TNF-α and IL-1β in the hippocampus of rats with vascular dementia.…”
Section: Effects Of Nimodipine In a Rat Vascular Dementia Modelmentioning
confidence: 99%
“…It has been shown that a relationship exists between changes in cognitive function and hippocampal damage, and that nimodipine treatment reversed the impairment of shortterm working memory caused by moderate hypoxia in mice. 32 Studies on the effect of nimodipine on rats with vascular dementia are, however, scarce. 18 The present study evaluated the effect of nimodipine treatment on levels of NF-κB, TNF-α and IL-1β in the hippocampus of rats with vascular dementia.…”
Section: Effects Of Nimodipine In a Rat Vascular Dementia Modelmentioning
confidence: 99%
“…It can expand the cerebral blood vessels, improve the cerebral circulation, and protect the brain. [6,7] Studies have shown that nimodipine could improve cognition in adult mice by reducing neuronal damage [8] and our previous research found pretreatment with nimodipine can prevent postoperative cognitive dysfunction (POCD) on aged rats by reducing hippocampal apoptosis rate. [9] However, its clinical effect remains to be discussed.…”
Section: Introductionmentioning
confidence: 99%
“…NIMO preserves performance in PA tasks, the radial maze, and the object recognition test after memory disruption induced by exposure to hypoxia 12,26…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we were interested in examining whether nimodipine (NIMO), an L-type calcium channel blocker that crosses the blood-brain barrier, would reduce the hypotension-induced impairment of learning and memory. Our previous investigation demonstrated that NIMO reversed transient cognitive dysfunction caused by moderate hypoxia in adult mice 12. In this study, we examined cognitive changes in animals subjected to nitroglycerin (NTG)-induced hypotension using a passive avoidance (PA) memory retention paradigm.…”
mentioning
confidence: 99%